Automating the construction of domain-specific modeling languages for object-oriented frameworks - Santos, A. L.; Koskimies, K.; Lopes, A. (Journal of Systems and Software, 2010)
The extension of frameworks with domain-specific modeling languages (DSML) has proved to be an effective way of improving the productivity in software product-line engineering. However, developing and evolving a DSML is typically a difficult and time-consuming task because it requires to develop and maintain a code generator, which transforms application models into framework-based code. In this paper, we propose a new approach for extending object-oriented frameworks that aims to alleviate this problem. The approach is based on developing an additional aspect-oriented layer that encodes a DSML for building framework-based applications, eliminating the need of implementing a code generator. We further show how a language workbench is capable of automating the construction of DSMLs using the proposed layer.